2017
DOI: 10.1007/s10353-017-0502-0
|View full text |Cite
|
Sign up to set email alerts
|

How many parathyroid glands can be identified during thyroidectomy?

Abstract: SummaryBackgroundThe purpose of this study is to provide guidance for medical experts regarding malpractice claims on permanent hypoparathyroidism by analyzing the number of parathyroid glands (PGs) identified during thyroidectomy and the clinical outcome.MethodsParathyroid findings were documented in a standardized protocol for 357 patients undergoing thyroidectomy and treated by a single specialized surgeon. The resected thyroid was routinely dissected for accidentally removed PGs with consecutive autotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
(44 reference statements)
0
17
0
2
Order By: Relevance
“…In our department, we usually perform limited lobectomy with isthmectomy + prophylactic CLND for patients with low-risk single small PTC. Hypoparathyroidism, an ongoing and frequently underestimated complication after thyroid operation, leads to hypocalcemia and serious medical problems[ 9 , 21 ]. Comparing hemithyroidectomy with all other surgical procedures, prolonged surgery (total thyroidectomy) and the diagnosis of malignancy are predictors of transient and permanent hypo-parathyroidism[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our department, we usually perform limited lobectomy with isthmectomy + prophylactic CLND for patients with low-risk single small PTC. Hypoparathyroidism, an ongoing and frequently underestimated complication after thyroid operation, leads to hypocalcemia and serious medical problems[ 9 , 21 ]. Comparing hemithyroidectomy with all other surgical procedures, prolonged surgery (total thyroidectomy) and the diagnosis of malignancy are predictors of transient and permanent hypo-parathyroidism[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eine Anzahl dargestellter Nebenschilddrüsen, die zur sicheren Vermeidung des Hypoparathyreoidismus erforderlich ist, ist nicht definierbar, da die Position der Epithelkörperchen einer großen Variationsbreite unterliegt -oft auch in deutlicher Distanz zur Schilddrüse bzw. auch außerhalb der Schilddrüsenloge und somit nicht identifizierbar [10]. Dieser Tatsache sind sich Chirurgen immer wieder bewusst, wenn aufgrund eines primären Hyperparathyreoidismus ein zu entfernendes Nebenschilddrüsenadenom nicht an typischer Stelle liegt.…”
Section: Hypoparathyreoidismusunclassified
“…Die Lokalisation der Nebenschilddrüsen kann äußerst exponiert sein. Sowohl das Erkennen als auch das vaskularisierte Erhalten der Epithelkörperchen kann selbst für den routinierten Schilddrüsenchirurgen eine Herausforderung darstellen [10,11]. Die dritte eingriffstypische Komplikation, die Nachblutung, ist zu einem seltenen Ereignis geworden und wird deshalb im Zuge der modernen Aufklärung häufig vernachlässigt.…”
Section: Introductionunclassified
“…The PTGs are variably located on the back of the thyroid gland, buried in the central neck compartment tissues and not easily distinguished from other adipose or connective tissues by the naked eye. Therefore, it is often damaged during tissue dissection or found in extracted specimens unintentionally . If the PTG is compromised, it leads to complications, such as hypoparathyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that inadvertent parathyroidectomy is approximately 18% during thyroid surgery, while patients experience temporary hypocalcemia (28.9%‐30.7%) and permanent hypocalcemia (1.6%‐9.6%) after thyroid surgery .…”
Section: Introductionmentioning
confidence: 99%